Pewarisan Sifat Densitas Stomata dan Laju Kehilangan Air Daun (rate leaf water loss RWL) pada Kacang Tanah (Arachis hypogaea L.) - Adisyahputra, Adisyahputra; Sudarsono, Sudarsono; Setiawan, Kukuh (Jurnal Natur Indonesia, 2011)
The aim of this research is to analyze and examine the inheritance of stomatal density trait and RWL as a variable in drought tolerance ofpeanut. The experiment was conducted by using cv. Kelinci that is sensitive genotype as female parent and US 605 which is tolerantgenotype as male parent, including population off spring from hybrid cv. Kelinci (P1) with US 605 (P2). Stomatal density was determinedby making leaf imprint and by observing leaf imprint under microscope. Relative water loss was determined by dipping peanut leaf in PEG40% for 48 hours. Result of the analysis showed that stomatal density and RWL were not only controlled by qualitative characters of majorgene, but also controlled by quantitative character of minor gene by polygenic with the complex gene action. Both characters seem toinfluence more as genetic factor and have high level fixation additive varians which can give the opportunity to obtain the tolerant offspring.